Rural and agricultural mechanization: A history of the spread of small engines in selected asian countries - Biggs, Stephen; Justice, Scott E. (International Food Policy Research Institute, 2015)
The past 50 years witnessed a remarkable spread of smaller-scale rural mechanization in some regions of South Asia, mostly characterized by the spread of single-cylinder diesel engines. These engines have been used for multiple purposes, such as providing power for shallow tubewell pumps, riverboats, two-wheel tractors, road and track transport vehicles, harvesters, threshers, grain mills, timber mills, and processing equipment. Diverse local market institutions for the buying and selling of water, tillage, transport, and many other services have been associated with the spread of smaller-scale rural equipment. Alongside these smaller-scale patterns of rural mechanization there have been significant increases in the intensity of agricultural production and in broader-based rural development. Despite this evidence, international and local policy debates do not reflect the significance of these patterns of rural mechanization for agricultural and rural development. We begin this paper with a discussion of three main generalizations arising from the spread of smaller-scale technology. We then take up policy issues and start by identifying four themes that explain why this smaller-scale mechanization transformation remained below the horizon in policy debates outside the regions where these changes have been taking place. We end the paper by discussing five ways forward in policy analysis.